The evolution of women's position in pre-Constitutional prose (from the period of Fath-Ali Shah to Mozaffar ad-Din Shah) - سید جعفر حمیدی; مریم عاملی رضایی (تاریخ ادبیات)
The general belief is that attention to the issue of women and its reflection in literature was formed during the Constitutional period. However, according to the historical texts, the reflection of women's issues in literature has gone through an evolutionary process. From the era of Fath Ali Shah, the fields of attention to women's issues began with the comparison between Iranian women and foreign women and went through a long and historical process until the era of Naser al-Din Shah and Muzaffar al-Din Shah, until it came to fruition in the Constitutional era. Prose, especially in the Naserid era, with its wide range of themes and tendency to simplistic writing, bore the burden of transformation in social themes, including women's issues. In this period, we are not only faced with the reflection of attention to women in all kinds of prose (travelogues, memoirs, playwriting and journalism) written by men, but for the first time, women also write in the form of letters, travelogues, treatises and memoirs to reflect their issues and prepare the ground for a more serious presence of women in the Constitutional period. The conflicts between supporters and opponents of changing the traditional roles of women created a discourse in the prose works of this period, which became the introduction to wider debates in the Constitutional period. This article examines the reflection of women and their related issues in the prose of the pre-Constitutional era.